Low-Voltage Low-Power Differential Difference Current Conveyor Transconductance Amplifier and Its Application to a Versatile Analog Filter - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz (My University, 2024)
This paper presents a new low-voltage low-power differential difference current conveyor transconductance amplifier (DDCCTA). The proposed DDCCTA utilizes a multiple-input gate-driven MOS transistor (MIGD-MOST) operating in the subthreshold region to achieve low supply voltage, minimum number of MOS differential pairs and minimum power consumption. To show the advantages of the proposed DDCCTA, it was used to realize a versatile analog filter. The filter uses three DDCCTAs, two grounded capacitors, and two grounded resistors to realize 65 transfer functions of low-pass, high-pass, band-pass, band-stop, and all-pass filters by appropriately selecting the input and output terminals without changing the filter topology. The filter also has the advantages of high-input impedance, which is ideal for voltage-mode circuits, independent control of the natural frequency and quality factor, and the ability to electronically tune the natural frequency. The proposed DDCCTA and versatile analog filter were designed and simulated using SPICE with TSMC 0.18μ m CMOS technology to verify the new circuits. The proposed filter uses ±0.5 V of supply voltage and 103μ W of power.
Keywords: analog filter; bulk-driven MOS transistor; Differential difference current conveyor transconductance amplifier; low-voltage low-power